Control of yellow and purple nutsedge in elevated CO2 environments with glyphosate and halosulfuron - Marble, S. Christopher; Prior, Stephen A.; Runion, G. Brett; Torbert, H. Allen (Frontiers in Plant Science, 2015)
Atmospheric concentrations of carbon dioxide (CO2) have significantly increased over the past century and are expected to continue rising in the future. While elevated levels of CO2 will likely result in higher crop yields, weed growth is also highly likely to increase, which could increase the incidence of herbicide resistant biotypes. An experiment was conducted in 2012 to determine the effects of an elevated CO2 environment on glyphosate and halosulfuron efficacy for postemergence control of purple and yellow nutsedge (Cyperus rotundus L. and C. esculentus L.). Both species of nutsedge where grown in 3.0-L containers under either ambient or elevated (ambient + 200 µmol mol-1) CO2 in open-top field chambers and treated with either 0.5×, 1.0×, or 1.5× of the manufacturer’s labeled rate of halosulfuron, glyphosate, or a tank mix of the two herbicides. The growth of both nutsedge species responded positively to elevated CO2, purple nutsedge had increased shoot and root dry weights and yellow nutsedge had increased shoot, root, and tuber dry weights and counts. Few treatment differences were observed among the herbicides at any of the rates tested. At three weeks following herbicide application, both purple and yellow nutsedge were adequately controlled by both herbicides and combinations at all rates tested, regardless of CO2 concentration. Based on this study, it is likely that predicted future CO2 levels will have little impact on the efficacy of single applications of halosulfuron or glyphosate for control of purple and yellow nutsedge at the growth stages described here, although scenarios demanding more persistent control efforts remain a question.